Profil Skabies pada Poli Rawat Jalan RS Awal Bros A. Yani Pekanbaru Periode Januari-Juli 2024 - Tampubolon, Benedicta; Arimbi, Endah Ageng; Pasaribu, Sarah Davita; Siahaan, Clarita Sonia; Lubis, Faridah Israwaty (Majalah Ilmiah METHODA, 2025)
Introduction: Scabies is a skin disease caused by Sarcoptes scabiei var hominis, and products. In developing countries, the highest incidence is in school-age children and adolescents. Development is influenced by low socio-economic conditions, poor hygiene, and a lack of knowledge about scabies. Objectives: This study aimed to determine the profile of scabies in outpatients at Awal Bros A. Yani Pekanbaru hospital. The benefits make it easier for health workers to educate and treat scabies patients. Methods: This is a retrospective descriptive study with medical record data for the period January-July 2024. The total population is 350 patients. Inclusions were new scabies patients diagnosed. Exclusions were patients' secondary diagnoses. Data variables were age, gender, symptoms, source of transmission, location, morphology, and management. Results: total sample was 133 patients. The most common age was early adolescence (24.8%), gender was male (52.6%), the largest source of infection was at school (54.9%), symptom was itching at night with rash (78.2 %), the location was found mostly in the upper and lower extremities (48.9%), morphology were papules and excoriations (41.4%), the most common treatment was combination of permethrin 5%, antihistamines, topical antibiotics (42.9%).